2003
DOI: 10.1113/jphysiol.2002.038703
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the force‐generating process in single fibres from frog skeletal muscle

Abstract: Generation of force and shortening in striated muscle is due to the cyclic interactions of the globular portion (the head) of the myosin molecule, extending from the thick filament, with the actin filament. The work produced in each interaction is due to a conformational change (the working stroke) driven by the hydrolysis of ATP on the catalytic site of the myosin head. However, the precise mechanism and the size of the force and length step generated in one interaction are still under question. Here we reinv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
138
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(163 citation statements)
references
References 40 publications
18
138
2
1
Order By: Relevance
“…The Q 10-force value from 10 to 20°C could not be used to extrapolate force generation at a higher temperature because the temperature dependence of the Q 10-force in these fibers is not known (Fig.4). However, this extrapolation should be viewed with caution, as force typically increases less as temperature increases further (Rall and Woledge, 1990;Piazzesi et al, 2003). With the stated linearity assumption, the value obtained is ~33kNm -2 for C. anna and 63kNm -2 for T. guttata.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Q 10-force value from 10 to 20°C could not be used to extrapolate force generation at a higher temperature because the temperature dependence of the Q 10-force in these fibers is not known (Fig.4). However, this extrapolation should be viewed with caution, as force typically increases less as temperature increases further (Rall and Woledge, 1990;Piazzesi et al, 2003). With the stated linearity assumption, the value obtained is ~33kNm -2 for C. anna and 63kNm -2 for T. guttata.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, muscle stiffness, interpreted as reflecting the number of attached crossbridges, increases much less with increasing temperature than does force generation, suggesting that the force generated per crossbridge increases with temperature (Ford et al, 1977;Kuhn et al, 1979;Goldman et al, 1987;Piazzesi et al, 2003;Decostre et al, 2005). However, Kawai and co-workers have proposed that force generated per crossbridge is independent of temperature and that the increase in muscle force with increased temperature is due to a shift in the crossbridge population (reviewed in Kawai, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, measurements of twitch and tetanus stress in gastrocnemius muscle from X. laevis demonstrated high thermal sensitivity between 5 and 20°C, with limited change from 20 to 30°C (Wilson et al, 2000). Previous work on Rana esculenta demonstrated that raising the temperature of single tibialis anterior muscle fibres from 2 to 12°C increased force output by a Q 10 of approximately 2 by increasing the number of cross-bridges that were in a force-producing state, without affecting the number of cross-bridges formed between the thick and thin filaments (Piazzesi et al, 2003). Such findings on single fibres help to explain the relatively large effects of temperature on whole-muscle force production during isometric activity at low temperatures in the present and previous studies.…”
Section: Isometric Forcementioning
confidence: 99%
“…Some of the adaptations to permit this are related to calcium channel function (Wang et al, 2002; Hauton et al, 2011). However, the force from motor proteins at low temperatures is reduced (Rall and Woledge, 1990;Piazzesi et al, 2003;Woledge et al, 2009), and yet ground squirrel hearts function at near-freezing temperatures, while simultaneously supporting cardiac performance when body temperature returns to euthermy, a temperature differential of over 30°C. Second, the activity of the heart, as quantified by heart rate, ranges from over 350-400 beats min -1 prior to hibernation, to a low of 4-5 beats min -1 during torpor.…”
Section: Echocardiogram and Myosin Of Hibernatorsmentioning
confidence: 99%